Chap 4: This is a REAL CHALLENGE!

Let's see who could simplify the following:
(x + 2)(y - 5)

10 comments:

  1. (x+2)(y-5)=x(y-5)+2(y-5)
    = (xy-5x)+(2y-10)
    = xy-5x+2y-10

    ReplyDelete
  2. (x + 2)(y - 5)
    = (x multiply by y)+(2 multiply by y)-(x multiply by 5)-(2 multiply by 5)
    =xy+2y-5x-10(Ans.)

    ReplyDelete
  3. This comment has been removed by the author.

    ReplyDelete
  4. (x+2)(y-5)
    = (x+2) x (y-5)
    =x x y - x x 5 +2 x y - 2 x 5
    = xy-5x+2y- 10

    ReplyDelete
  5. (x + 2)(y - 5)
    =[xy+x(-5)]+[2y+2(-5)]
    =(xy-5x)+(2y-10)

    ReplyDelete
  6. Wow! Well Done, people :D
    Looks that the expression is not as complex as I've thought of :D
    The question falls in the category beyond what's described in Chapter 5 (i.e. expansion involving 2 brackets).

    PS:
    Zhi Chao: Just one more step, you would have expressed your answers in the simplest form :D

    ReplyDelete